The Influence of Madrasah Organizational Characteristics on the Principal Decision-Making - Nuraeni, Reni; Manggala, Trisna Saputra; Mutmainah, Nur Afifah; Wulandari, Riana Trisna (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to determine how big the relationship between organizational characteristics and the decision-making process of the head of the madrasa as a leader. Principals have the responsibility for making decisions to improve management and develop madrasah. The method used in this research is quantitative with non-experimental research methods (survey). Questionnaires were given to 34 respondents who are teachers at Madrasah Aliyah Al-Mustaqiem. The results showed that madrasas applied indicators of organizational characteristics, but the relationship between organizational characteristics and the principal's decision was not significant. The components that exist in the characteristics of the madrasa organization need to be evaluated and improved. Other factors are more dominant and influence the decision-making of the madrasah principal. This is an opportunity for further research to examine which factors are more dominant in the principal's decision-making as a determinant of improving organizational quality.